Peran Pasraman Sebagai Lembaga Pendidikan Formal Dalam Membentuk Karakter Religius Peserta Didik - Naraditya, Ryan; Paramarta, I Made (Jayapangus Press, 2021)
Education in Indonesia is an activity that must be carried out by children, in Indonesia itself children are required to get education at school for 12 years, but education is not only in school but can be obtained from the environment, and also family. Education is divided into three namely formal, non-formal, and informal education. Religious education is something that is very important for children to get which can support the behavior and behavior and manners of children. Hindu religious education has a very important role and has a share in achieving the goals of this nation. Formal Pasraman as an educational institution based on Hinduism has a very important role in shaping the character of students. This research uses qualitative research with literature study. The results of this study indicate that Pasraman activities, as a formal educational institution, are an effort to provide education to the younger generation of Hindus in a simple form in accordance with local traditions, customs, dresta, conditions. With this formal pasraman, it is hoped that the younger generation of Hindus can get more Hindu religious education, and no longer hesitate because the formal pasraman has the same position as formal schools in general, so that the goals of this nation can be achieved and have the next generation of the nation that has a religious spiritual character.